Weed control, yield and profitability of peas as influenced by integrated chemical and mechanical methods - Akhtar, Naveed; Zohaib, Ali; Tabassum, Tahira; Babar, Babar Hussain; Nawaz, Muhammad; Ramzan, Hafiz Naveed; Iqbal, Muhammad; Iqbal, Saba; Shafiq, Muhammad Faisal; Latif, Muhammad Tahir; Nawaz, Mohsin (Journal of Pure and Applied Agriculture, 2025)
Pre- or post-emergence herbicides alone are insufficient to manage heavy infestation of diverse weed flora in peas. Integrated use of chemical weed control along with mechanical weeding could give better weed management. Therefore, this study aimed to evaluate the comparative effects of using post-emergence herbicides (flumetsulam and bentazone) or rotary weeding, either alone or in combination with pre-emergence herbicides (s-metolachlor and pendimethalin) on yield of peas. Results revealed that mechanical weed control with rotary weeder [15, 30 and 45 days after sowing (DAS)] was the most effective with the greatest reduction in total weed density and dry biomass (94-96%), and increase in pods plant-1, fresh pod weight, fresh pod yield (144-185%), and benefit-cost ratio (1.88). Pre-emergence application of s-metolachlor and/or pendimethalin followed by post-emergence application of bentazone could be ranked second regarding weed control; however, pre-emergence application of pendimethalin + post-emergence application of bentazone gave better yield and profitability than pre-emergence application of s-metolachlor + post-emergence application of bentazone. A significant negative relationship of total weed dry biomass with fresh pod yield indicated that yield loss was associated with weed flora and could be reduced by better weed control. Conclusively, sole rotary weeding (15, 30 and 45 DAS) or integration of pre-emergence pendimethalin application with post-emergence bentazone application gave better weed control along with higher pod yield and profitability of peas.